A Sea-Sami's story. From fishing-farmer to miner. From Sea-Sami to Norwegian? - Evjen, Bjørg (University of Tromsø, 2007)
Presentation at the 8th annual Forum for Development Cooperation with Indigenous Peoples, which commenced the 18th-19th of October 2007. The Centre for Sámi Studies hosted the conference at the University of Tromsø, Norway. Full conference report available at http://hdl.handle.net/10037/2995